Distributed formation shape control of multi-robot systems - Cao, Kun (Nanyang Technological University, 2021)
Multi-robot system enjoys broad applications in civilian, industrial, and military areas, as team cooperation offers significant improvements of efficiency and system robustness. As an essential problem of multi-robot researches, the formation control problem that requires robots to form a desired formation shape has been intensively investigated in the past two decades. According to the type of constraints specifying the desired formation shape, most of the existing results can be classified as: 1) position-based; 2) displacement-based; 3) distance-based; and 4) bearing-based. However, few of these control laws can handle the formation shape control problem where the formation of the multi-robot system converges to the desired shape up to similar transformations (translation, rotation, scaling and reflection). The above motion freedoms enable us to maneuver the entire team by controlling a few agents called leaders when operating in unstructured environments. Moreover, the cost of sensors with different modalities and capabilities can vary significantly and so does the aggregate budget for large-scale multi-robot systems. Motivated by these issues, this thesis is dedicated to studying distributed formation shape control with full degrees of freedom by exploring the trade-off between requirements on sensor capabilities and sensing / communication graph topologies.